We are given that
points through which parabola is passing
(-1,1) and (1,-3)
so, we have
x1=-1 ,y1=1
x2=1 , y2=-3
we can find average rate of change by using formula
![A=(y_2-y_1)/(x_2-x_1)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/l4w3s4fv3ipau7e025za5sqqx5fzb67rxy.png)
now, we can plug values
![A=(-3-1)/(1+1)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/u1eb420byehpgbcu2gciyv4qyyfu3172uo.png)
![A=(-4)/(2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/hz84iyb7qy3ojta4jgw4zu6eu5ve6vybww.png)
![A=-2](https://img.qammunity.org/2019/formulas/mathematics/middle-school/fevokdo81bwd2rzqcfxct3v80a889csya6.png)
So, the average rate of change from -1 to 1 is -2...........Answer